Logarithmic and exponential functions / Aishah Mahat - Mahat, Aishah (UiTM Cawangan Johor Kampus Pasir Gudang, 2024)
This e-book, Logarithmic and Exponential Function aimed to help students in mathematic subject. Targeted users for this module is students who take foundation course. This e-book is divided into two topics which Logarithmic Function and Exponential Function. Mathematical tips and formulas will be placed in accordance to the subtopics whilst each questions will be displayed based on the syllabus carried out during the lesson. At the end of each topic, targeted students should meet up with the lecturer to discuss over the solution of mathematics problem. With the existence of this e-book, hopefully it will be beneficial and give positive impact towards teaching and learning for students and lecturers as a whole.